Fast forward early 20th-century Aotearoa - Kessell, Terri (Tangata Whenua, 2012)
Resource for year 9 to 10 students focusing on the period of rapid social change and development in the first half of the 20th century, including both World Wars and the Great Depression. Suggested level: junior secondary